2012
DOI: 10.1016/j.bjid.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and antimicrobial susceptibility of Staphylococcus aureus nasal isolates from medical students in Cartagena, Colombia

Abstract: Staphylococcus aureus (SA) remains a major cause of nosocomial and community-acquired infections worldwide. Nasal carriage of this bacterium among hospital personnel constitutes an important source for nosocomial infections. A cross-sectional study enrolling the whole medical student population (n=387) of the School of Medicine at the Universidad de Cartagena, Colombia, was conducted to evaluate the carriage rates of both methicillin sensitive- and methicillin resistant-SA, the frequency of Panton-Valentine le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 43 publications
4
26
2
4
Order By: Relevance
“…The nasal carriage rate of MRSA in international studies in students ranged from 0% -6.7%. 3,[9][10][11]14 Amongst the Indian studies, a study by Bhaskaran reported a MRSA colonization of 8.6% among medical students while another study by Shrivastav et al 2015 reported the MRSA carriage rate to be 1.1%, which is much lower than our study. 6,15 The present study showed no significant difference in carriage rate of S.aureus and MRSA among male and female students.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The nasal carriage rate of MRSA in international studies in students ranged from 0% -6.7%. 3,[9][10][11]14 Amongst the Indian studies, a study by Bhaskaran reported a MRSA colonization of 8.6% among medical students while another study by Shrivastav et al 2015 reported the MRSA carriage rate to be 1.1%, which is much lower than our study. 6,15 The present study showed no significant difference in carriage rate of S.aureus and MRSA among male and female students.…”
Section: Discussioncontrasting
confidence: 71%
“…Various studies have reported S.aureus nasal carriage in medical students ranging from 10%-39%. 3,6,[10][11][12][13] The colonisation rate of MRSA in the present study was found to be 12.66% amongst the medical students. The nasal carriage rate of MRSA in international studies in students ranged from 0% -6.7%.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…iki 63,2 proc. [17,19,23,24,27]. Didelis šio tyrimo metu išskirtų padermių jautrumas nustatytas ir klindamicinui bei tetraciklinui (95 proc.).…”
Section: Rezultatų Aptarimasunclassified
“…Existen diversas poblaciones con riesgo de presentar infección por esta bacteria tales como: escolares, presos, personas con cáncer, personal del área de la salud, estudiantes de medicina, entre otros [13,14,15,16,17,18,19,20]. En el año 2005, Castro y cols realizaron una investigación en estudiantes de quinto semestre de Bacteriología de la Corporación Universitaria Rafael Núñez, encontrando una frecuencia de portación de S. aureus de 29,8% [21]; en 2010 se evaluó nuevamente la portación en estudiantes de Bacteriología de primero a séptimo semestre de esta institución, encontrándose una frecuencia de portación de Staphylococcus aureus sensibles a meticilina (SASM) de 14,9 % [22], debido a que no se conoce la variación de la portación en estudiantes de Bacteriología a medida que estos avanzan en los semestres y están expuestos al ambiente del laboratorio clínico, el grupo investigador decidió evaluar la variación en el estado de portación nasal de esta bacteria en estudiantes del programa de Bacteriología de la Corporación Universitaria Rafael Núñez, que fueron definidos como portadores en el año 2010.…”
Section: Introductionunclassified